Aquatic Plants for Acid Mine Drainage Remediation in Simulated Wetland Systems - Munawar, Ali; Leitu, Farkhruddin Okte; Bustamam, Hendri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Aquatic plant is an important component of a constructed wetland system for treating acid mine drainage (AMD).This study was conducted to investigate the remediation effects of planting three aquatic plants species on AMDquality in simulated wetland systems. Simulated wetland systems were constructed using 10-L plastic containersas growth media comprising mixed-organic substrates and aquatic plant species as planting treatments. Thetreatments involved individual plantings with Fimbristilys hispidula (Vahl) Konth, Mariscus compactus (Retz) Druce,and Typha angustifolia L., and mixed-planting with a combined three-plant species. As the control was the unplantedmedia. The plants were continuously flooded with very acidic AMD collected from a mine pit in PT TambangBatubara Bukit Asam, South Sumatra. During the experiment, the acidity (pH), oxidation reduction potential (Eh),and electrical conductivity (EC) of the flooding AMD were measured after 24 hours of the flooding, and thenbiweekly until the plants entered their reproductive stage. To estimate Fe removed by plants, AMD samples weretaken from both planted and unplanted systems for total dissolved Fe analyses. The data revealed some remediationeffects of planting aquatic plants on AMD in the wetland treatment systems. The presence of plants in the wetlandsystem appeared to induce oxygen diffusion to surrounding roots, which might result in Fe precipitation on rootsurface. Although no differences among planting treatments, Fe removals by plants highly correlated (R2=0.92)with the production of plant biomass.